Culture of Student Daily Infaq on Education Quality Development at MDTA: (Study at MDTA Al-Khairiyah Bujang Gadung Cilegon) - Sayuti (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2023)
Madrasah Diniyah Takmiliyah Awwaliyah (MDTA) is one of the non-formal educational institutions under the auspices of the Ministry of Religion. The lack of attention from the government makes the condition of madrasas even more alarming. Weak resources and management, as well as the unavailability of a budget in the world of education which is something that is inseparable, makes this institution worse off. This study uses a qualitative descriptive methodology with an interview, observation, and documentation approach. The results show that due to a lack of attention from the government, institutional life has been fully funded by contributions or infaq from the local community. So with the daily infaq culture, students contribute significantly in helping the development of the quality of education at Madrasah Dinyah Takmiliyah Awwaliyah Al-Khairiyah Bujang Gadung, Cilegon Banten.